Antihypertensive phytocomplexes of proven efficacy and well-established use: Mode of action and individual characterization of the active constituents. (February 2020) - Micucci, M.; Bolchi, C.; Budriesi, R.; Cevenini, M.; Maroni, L.; Capozza, S.; Chiarini, A.; Pallavicini, M.; Angeletti, A.
Abstract: Hypertension has become the leading risk factor for worldwide cardiovascular diseases. Conventional pharmacological treatment, after both dietary and lifestyle changes, is generally proposed. In this review, we present the antihypertensive properties of phytocomplexes from thirteen plants, long ago widely employed in ethnomedicines and, in recent years, increasingly evaluated for their activity in vitro and in vivo, also in humans, in comparison with synthetic drugs acting on the same systems. Here, we focus on the demonstrated or proposed mechanisms of action of such phytocomplexes and of their constituents proven to exert cardiovascular effects. Almost seventy phytochemicals are described and scientifically sound pertinent literature, published up to now, is summarized. The review emphasizes the therapeutic potential of these natural substances in the treatment of the 'high normal blood pressure' or 'stage 1 hypertension', so-named according to the most recent European and U.S. guidelines, and as a supplementation in more advanced stages of hypertension, however needing further validation by clinical trial intensification. Graphical abstract: Image 1 Highlights: Antihypertensive properties of phytocomplexes from 13 plants are presented. Almost 70 constituents with proved antihypertensive action are individuated from such complexes. Selection has been made on the criterion of available evidences of in vitro, in vivo and clinical effectiveness. Their potential in high-normal BP treatment and as a supplementation in hypertension is discussed.